H2S- and NO-Signaling Pathways in Alzheimer's Amyloid Vasculopathy: Synergism or Antagonism? - Salmina, Alla B.; Komleva, Yulia K.; Szijártó, István A.; Gorina, Yana V.; Lopatina, Olga L.; Gertsog, Galina E.; Filipovic, Milos R.; Gollasch, Maik (Frontiers in Physiology, 2015)
Alzheimer's type of neurodegeneration dramatically affects H2S and NO synthesis and interactions in the brain, which results in dysregulated vasomotor function, brain tissue hypoperfusion and hypoxia, development of perivascular inflammation, promotion of Aβ deposition, and impairment of neurogenesis/angiogenesis. H2S- and NO-signaling pathways have been described to offer protection against Alzheimer's amyloid vasculopathy and neurodegeneration. This review describes recent developments of the increasing relevance of H2S and NO in Alzheimer's disease (AD). More studies are however needed to fully determine their potential use as therapeutic targets in Alzheimer's and other forms of vascular dementia.